Das cosmologias de partos/nascimentos : um estudo sobre saberes relacionados às concepções de parteria contemporânea - Nascimento, Thayane Cazallas do (Universidade do Vale do Rio dos Sinos, 2018)
The thesis aims to understand the construction of knowledge involved and developed in a birth cosmology “in tradition”, present in an alternative space to the predominant medical-hospital model in contemporary society. The empirical basis of this thesis was based on the monitoring of the activities developed by the wheel of couples and pregnant women in the Flor da Vida space, in Porto Alegre, Rio Grande do Sul. The proposal known as childbirth "in tradition" involves the realization of a birth that considers both the experience of those of the gestate and the baby born as a spiritual event. Its definition as "in tradition" is a reference to the model of teachings and procedures from a traditional midwife who teaches her knowledge, linked to the practice of "helping to give birth" to other midwives who follow "in" their tradition. The results of this investigative trajectory are organized as follows: I first present the theoretical conceptual discussion that bases the analyzes performed, especially the notion of birth cosmology and present the analytical categories guiding the research: Interventionism, technicalism and medicalization of childbirth; the relationship between Ecofeminism and Education and the notion of empowerment in a feminist perspective. Following, I discuss the proceeding of the Center for the Integration of the Being/CAIS of Childbirth and the School of Knowledge, Culture and Ancestral Tradition/ESCTA, trying to analyze the impact of their activism in the defense of the traditional childbirth and in the initial and continued formation of midwives and doulas “in tradition”. Next I present the considerations about the accompaniment in the search location, approaching the formative trajectory of midwives and doulas "in tradition" of ESCTA; the conception of the spiritual mission of this birth; the conceptions and experiences of this cosmology and its reach beyond childbirth; the organization of the traditional midwife in Rio Grande do Sul and I finish trying to analyze the new horizons of another birth culture and diffusing traditional birth in the contemporary urban environment. As a conclusion, the study shows that childbirth and birth, as well as gestation within reflections from the Flor da Vida space, amplify the perceptions and the practices of the Education area. The knowledge about childbirth and birth and the educational knowledge are 10 interconnected in the development of an interdisciplinary thought that is also a pedagogical knowledge, taking into account the spirituality and the full presence of being at the time of childbirth and birth.
Keywords: Educação e Parteira; Parteira “na tradição”; Cosmologias de partos/nascimentos; Education and Midwife; Midwife “in tradition”; Childbirth Cosmologies; ACCNPQ::Ciências Humanas::Educação